Model for Measuring Employee Performance on the Quality of Health Services at the North Aikmel Community Health Center, East Lombok Regency - Azkar, Azkar; Achmad Lukman Hakim; Pathurrahman, Pathurrahman (Jurnal EduHealth, 2024)
Puskesmas is a health service facility for the community that must pay attention to the quality of service. Accreditation is an acknowledgment of the quality of Puskesmas health services. North Aikmel Community Health Center is one of the Community Health Centers in East Lombok District that has not been accredited in 2022, with the number of staff is 94 people and ASN only 19 people. The research design utilized a quantitative cross-sectional approach, collecting data through a questionnaire measured on a Likert scale. Data analysis employed Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) approach through the smart-PLS4 application. The hypothesis test results show that the work environment has a positive but not significant influence on service quality (T-statistic 0.57), work motivation has a positive but not significant influence on service quality (T-statistic 0.89), work commitment has a positive and significant influence on service quality (T-statistic 2.75), and employee performance has a positive and significant influence on service quality (T-statistic 3.06). The magnitude of the influence of the environment, work motivation, work commitment, and employee performance on service quality is 67.8%. Conclusion: There is an influence of the work environment, work motivation, work commitment, and employee performance on the quality of health services at the Aikmel Utara Community Health Center in East Lombok District, with employee performance being the dominant factor affecting the quality of health services.